2008
DOI: 10.1007/s10620-008-0528-z
|View full text |Cite
|
Sign up to set email alerts
|

Transmucosal Gastric Leak Induced by Proton Pump Inhibitors

Abstract: Despite their remarkable safety profile and lack of clinical side effects, proton pump inhibitors (PPIs) induce a transmucosal gastric leak to non-electrolyte probes of various sizes. The ex vivo addition of PPIs to isolated rat gastric corpus increases transmucosal permeability in a dose-dependent manner, which corresponds with PPIs' dose-dependent inhibition of acid secretion. Upon the addition of omeprazole, lansoprazole, or esomeprazole, a small decrease in transepithelial resistance and the concomitant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
4
24
0
Order By: Relevance
“…As a result, luminal contents can more easily penetrate the lamina propria causing an immune and/or inflammatory reaction. Esomeprazole has been shown to increase paracellular permeability in the upper gastrointestinal tract in vitro [16] and in vivo in humans [17]. The intestinal barrier function has been shown to be a key factor in maintaining intestinal homeostasis.…”
Section: Proteins Other Than Hmentioning
confidence: 99%
“…As a result, luminal contents can more easily penetrate the lamina propria causing an immune and/or inflammatory reaction. Esomeprazole has been shown to increase paracellular permeability in the upper gastrointestinal tract in vitro [16] and in vivo in humans [17]. The intestinal barrier function has been shown to be a key factor in maintaining intestinal homeostasis.…”
Section: Proteins Other Than Hmentioning
confidence: 99%
“…As described above, one of its already-reported properties is that only molecules smaller than 4000 daltons can pass [5]. This statement however does not take into account the complexities of the molecule's charge, shape and hydrophobicity, all of which can prevent its permeation even though it may be sufficiently small in overall mass.…”
Section: Discussionmentioning
confidence: 98%
“…The leak was observed to set in quickly after initiation of esomeprazole therapy (3-5 days) and reverse equally quickly after cessation of medication. Subsequent animal model studies, also by our group, showed the following properties of this leak: 1) it is bidirectional; 2) it allows molecules as large as 4,000 daltons to permeate, but not molecules 10,000 daltons or larger; 3) it manifests a similar dose dependence to that for inhibition of acid secretion; 4) it occurs near instantaneously if the proton pump inhibitor (PPI) concentration is sufficiently high; 5) it is a general property of PPIs and not specific to only one individual PPI; 6) it requires a luminal fluid pH below 5.0 [5]. These results confirm and extend the earlier findings of Hopkins et al (2002) [6] using rat gastric corpus, the first indication that omeprazole was inducing gastric transepithelial leak.…”
mentioning
confidence: 99%
“…As a result, luminal contents can more easily penetrate the lamina propria causing an immune and/or inflammatory reaction. Esomeprazole has been shown to increase paracellular permeability in the upper gastrointestinal tract in vitro (14) and in vivo in humans (15). Increased paracellular permeability has been observed in MC and is considered a key component in the induction of diarrhea (16).…”
Section: Discussionmentioning
confidence: 99%